Inter sphincter rectal resection with and without malone antegrade continence enema in patients with low rectal cancer: A randomized, prospective, single-blind, parallel clinical trial - Mina Alvandipour; Mohammad Yasin Karami; Mahmood Azadfar; Jamshid YazdaniCharati (Babol University of Medical Sciences, 2022)
Background: Fecal incontinence is the main morbidity of inter-sphincteric resection (ISR) in ultra-low rectal cancer. Malone Ante grade Continence Enema (MACE) has been proposed for these patients. We aimed to compare the quality of life outcomes in cases with ultra-low rectal cancer who had undergone ISR±MACE. Methods: The current randomized clinical study was accomplished for two years from December 2016 to February 2018 in Imam Khomeini Hospital (Sari City, I.R.Iran) on 30 patients (15 in each group) with rectal cancer. The inclusion criteria of the study were stage 1 and 2a of low rectal cancer with type 2 and 3 of Rullier's classification, those who received neoadjuvant chemo radiotherapy. The exclusion criteria were comorbidity diseases, immune deficiency, poor follow-up. The follow-up period was one year. The Quality of Life (Qol) was reported as primary endpoint. The EORTC QLQ-C30 score and Wexner questionnaires were used. SPSS Version 22 was used. A p-value less than 0.05 was considered statistically significant. Results: The mean age of patients was 56.23±8.72 years. The overall Qol score was better in the ISR-MACE (P=0.023). The overall Qol was lower in women than in men in both groups. Low anterior resection syndrome score was lower in the ISR plus MACE group than the ISR group (P=0.030). The Wexner score revealed better scores in the ISR with MACE group than the ISR without MACE group (p<0.0001). Conclusion: Patients who underwent ISR plus MACE surgery had better defecation control and better quality of life than patients without MACE.